Combination of Endoscopic Resection and Radiofrequency Ablation for the Treatment of Esophageal Squamous Cell Neoplasia With Multiple Lugol-Voiding Lesions - Chen, Zhihao; Dou, Lizhou; Liu, Yong; Zhang, Yueming; He, Shun; Xue, Liyan; Wang, Guiqi (Frontiers in Oncology, 2021)
Background Local recurrence of esophageal squamous cell neoplasia (ESCN) and metachronous ESCN was associated with severe background esophageal multiple Lugol-voiding lesions (LVLs) even though the primary early ESCNs were treated with endoscopic resection (ER). The aim of this study is to explore the feasibility and effectiveness of combination treatments of ER and radiofrequency ablation (RFA) in patients with early ESCNs with synchronous multiple LVLs. Methods A total of 329 patients with early ESCNs and synchronous multiple LVLs received ER combined with RFA from September 2010 to September 2020. Clinical and pathological features and treatment outcomes were retrospectively reviewed using medical records. Factors associated with background esophageal multiple LVLs before combined treatment were analyzed. Results The proportion of complete response (CR) was 96.7% after primary RFA, while 90.3% patients achieved CR for the last endoscopic examinations regardless if inside or outside the treatment area (TA). Degeneration of background esophageal multiple LVLs occurred in 70.2% of patients. The grade of background esophageal multiple LVLs before combined treatment was closely related to gender, smoking, and drinking. The incidence of metachronous ESCNs outside the TA of ER and local recurrence in the TA of ER was 3.9% and 1.2%, respectively. Conclusions Prophylactic RFA treatment of multiple LVLs together with ER treatment of the primary ESCNs may be effective in reducing the incidence of metachronous ESCNs and local recurrence through improving the background esophageal mucosa.